When to Perform Fusion Short of the Pelvis in Patients with Cerebral Palsy?: Indications and Outcomes. Issue 2 (14th April 2023) - Badin, Daniel; Baldwin, Keith D.; Cahill, Patrick J.; Spiegel, David A.; Shah, Suken A.; Yaszay, Burt; Newton, Peter O.; Sponseller, Paul D.
Abstract : Background: Patients with scoliosis secondary to cerebral palsy (CP) are often treated with posterior spinal fusion (PSF) with or without pelvic fixation. We sought to establish criteria to guide the decision of whether or not to perform fusion "short of the pelvis" in this population, and to assess differences in outcomes. Methods: Using 2 prospective databases, we analyzed 87 pediatric patients who underwent PSF short of the pelvis from 2008 to 2015 to treat CP-related scoliosis and who had ≥2 years of follow-up. Preoperative radiographic and clinical variables were analyzed for associations with unsatisfactory correction (defined as pelvic obliquity of ≥10°, distal implant dislodgement, and/or reoperation for increasing deformity at 2- or 5-year follow-up). Continuous variables were dichotomized using the Youden index, and a multivariable model of predictors of unsatisfactory correction was created using backward stepwise selection. Finally, radiographic, health-related quality-of-life, and clinical outcomes of patients with fusion short of the pelvis who had neither of the 2 factors associated with unsatisfactory outcomes were compared with those of 2 matched-control groups. Results: Deformity correction was unsatisfactory in 29 of 87 patients with fusion short of the pelvis. The final model included preoperative pelvic obliquity of ≥17° (odds ratio [OR], 6.8; 95% confidence interval [CI], 2.3 to 19.7; p < 0.01) and dependent sitting status (OR, 3.2; 95% CI, 1.1 to 9.9; p = 0.04) as predictors of unsatisfactory correction. The predicted probability of unsatisfactory correction increased from 10% when neither of these factors was present to a predicated probability of 27% to 44% when 1 was present and to 72% when both were present. Among matched patients with these factors who had fusion to the pelvis, there was no association with unsatisfactory correction. Patients with independent sitting status and pelvic obliquity of <17° who had fusion short of the pelvis had significantly lower blood loss and hospital length of stay, and better 2-year health-related quality-of-life scores compared with matched controls with fusion to the pelvis. Conclusions: In patients with scoliosis secondary to CP, pelvic obliquity of <17° and independent sitting status are associated with a low risk of unsatisfactory correction and better 2-year outcomes when fusion short of the pelvis is performed. These may be used as preoperative criteria to guide the decision of whether to perform fusion short of the pelvis in patients with CP. Level of Evidence: Prognostic Level III . See Instructions for Authors for a complete description of levels of evidence.